2015
DOI: 10.1111/jace.14042
|View full text |Cite
|
Sign up to set email alerts
|

Study on Reduction of MoO2 Powders with CO to Produce Mo2C

Abstract: Molybdenum hemicarbide (Mo2C), which is widely applied in steel and metal ceramics as well as catalysts, was successfully synthesized by using a simple method of reducing MoO2 powders by CO. It was found that the final reduction product was all Mo2C under both isothermal and nonisothermal conditions. However, the reduction mechanisms were significantly different at lower and higher temperatures: at lower temperatures (1070 to 1342 K), reduction of MoO2 to Mo2C followed a one‐step reaction (simultaneous reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…10) Because of its high hardness, high melting point, and wear resistance, Mo 2 C has been widely applied as a reinforcement material in in steel and in metal ceramics. 11,12) It is worth mentioning that Mo 2 C is also an effective grain growth inhibitor due to its high solubility and mobility in the metal matrix phase. 13) Our previous studies indicated that heat treatment can be used to increase the strength and hardness of as-sintered P/M alloy steel.…”
Section: Mechanical Properties and Microstructures Of Mo 2 C Strengthmentioning
confidence: 99%
“…10) Because of its high hardness, high melting point, and wear resistance, Mo 2 C has been widely applied as a reinforcement material in in steel and in metal ceramics. 11,12) It is worth mentioning that Mo 2 C is also an effective grain growth inhibitor due to its high solubility and mobility in the metal matrix phase. 13) Our previous studies indicated that heat treatment can be used to increase the strength and hardness of as-sintered P/M alloy steel.…”
Section: Mechanical Properties and Microstructures Of Mo 2 C Strengthmentioning
confidence: 99%
“… 40 To circumvent this issue, our study involves the prior synthesis of the Mo carbide by contacting the Mo/HZSM-5 pre-catalyst with carbon monoxide (CO) at a high temperature (780 °C). Indeed, carbon monoxide has been reported to carburize Mo oxides to Mo 2 C. 41 43 We will demonstrate by a combination of online mass spectrometry (MS) and operando X-ray absorption spectroscopy that the Mo (oxy-)carbide produced via CO carburization and CH 4 activation is equivalent. We report more direct structural characterization of the active site using 13 C NMR.…”
Section: Introductionmentioning
confidence: 99%
“…it has been widely applied as a reinforcement 1 material in metal ceramics [15,16]. Moreover, Mo 2 C is also the most effective grain growth inhibitor due to its excellent solubility and mobility in the metal matrix phase during the liquid phase sintering (LPS) of the PM process [17,18].…”
Section: Introductionmentioning
confidence: 99%